Lung function trajectories in children with pulmonary TB and non-TB lower respiratory tract infections - I.J. Courtney; M. Palmer; R. Swanepoel; C.J. Lombard; M. van Niekerk; R. Dunbar; E.D. McCollum; H.S. Schaaf; A. Gie; P. Goussard; A.C. Hesseling; V.W. Jongen; et al. (IJTLD Open)
BACKGROUND: This longitudinal study compared lung function in children with pulmonary TB (PTB), children with non-TB lower respiratory tract infections (LRTIs) and healthy controls. METHODS: Children aged 4–13 years presenting with presumed PTB and their healthy siblings who could perform spirometry were included. Children were classified as having TB, non-TB LRTIs after careful evaluation and during follow-up. Spirometry measurements were completed at baseline and at subsequent study visits during 52 weeks of follow-up. Measurements included forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), and FEV1/FVC using 2022 race-neutral Global Lung Initiative reference ranges. RESULTS: Of 143 children, 46 had TB, 64 had non-TB LRTIs, and 33 were healthy controls. The median age was 6 years (IQR 5–9) and 10 (7%) were living with HIV. Restrictive spirometry patterns were common in both symptomatic groups at the end of follow-up, with a significantly lower FVC in children with TB compared to controls. In multivariable analysis adjusted for time and study group, FEV1 and FVC decreased for both the TB and non-TB LRTI groups, compared to healthy controls. CONCLUSION: Lung-function trajectories were similar between children with TB and non-TB LRTI, with low FVC one-year after diagnosis.